A practitioner researcher's opportunities and challenges in accessing interpretive case participants in a public healthcare setting. Issue 1 (22nd May 2019) - Doyle, Louise
Abstract : Purpose: The purpose of this paper is to document the opportunities and challenges of a practitioner researcher in accessing interpretive case participants in the public healthcare sector in Ireland. Design/methodology/approach: The paper documents the research design and implementation phases of a longitudinal interpretive research project with specific focus on, research ethics, preparing for data collection, identifying and recruiting the research participants and analysis of the findings based on the specific nuances of the public health context and design considerations. Considerations as an insider researcher in a large public organisation are also presented. Findings: Conducting interpretive research in a healthcare setting presents both opportunities and some challenges; key amongst these is agreed access to research participants. In addition, with research taking place in a healthcare environment, the potential for disclosure of information regarding something harmful to patients or of a criminal nature exists. This risk can be addressed through the ethical approval process documented in this paper. Insider researcher considerations are also explored focussing on the specific nuances affiliate to carrying out a longitudinal interpretive study in a public healthcare setting. Research limitations/implications: Insights for those wishing to conduct longitudinal interpretive case research in the public healthcare setting are included. The implications for enhanced engagement with interpretive research in this context are addressed. Originality/value: Through documenting the opportunities and challenges of a practitioner researcher in accessing research participants in the public healthcare sector, this paper discusses insider researcher considerations and seeks to address concerns in the literature regarding insufficient detail relating to interpretive research design and implementation in healthcare contexts.